Degradation of Phenol By Photolysis Using N-doped TiO2 Catalyst - Safni Safni; Mechy Rezita Wahyuni; Khoiriah Khoiriah; Yulizar Yusuf (Molekul, 2019)
Phenol (C6H5OH) is a common contaminant in wastewater. In certain concentrations, phenol can inhibit the activity of microorganisms and give adverse effects tohumanhealth, such as liver and kidney damage, perfect heart rate, and lower blood pressure. In this study, phenol was degraded with andwithoutN-doped TiO2under photolysis UV-light (10 Watts, λ = 365 nm) and visible-light (13 watt Philips, lux= 1400, λ = 465-640 nm)irradiation. The reductionof phenol concentrationwas measured by a UV-Vis spectrophotometer at a wavelength 200-400 nm. Some parameters such as catalyst dose, irradiation timesand type of light sources were studied. The XRD and DRS UV-Vis characterization confirmthat the nitrogen modified of titania catalyst potentially actives in visible-light. The N-doped TiO2is able to catalyze and improve the efficiency of phenol degradation in photocatalysissystem. Phenol with initialconcentration 8 mg/L was degraded by 33.89% and 30.51% without catalyst and increased to be 90.8% and 67.80%by additionof 15 mg N-doped TiO2catalyst under UV-light and visible-lightfor 210 minutes photolysis, respectively. From the results,irradiation using UV-light achieveshigherefficiency than visible-lightonphenol degradation.